(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Breast cancer is a complex disease, many etiological agents are proposed to play a role in its pathogenecity, one of these factors is cytokines. Objectives:In the present study we measured the concentration of IL-6 and IL-10 in serum of breast cancer patients and examined their association with clinicopathological variables including stages of the disease and estrogen/progesterone receptor (ER, PR) expression on tumor cells, to determine whether it associate with the disease progression. Subjects and Methods: The study included 80 subjects, it comprised of 45 Breast cancer patients, 12 patients with benign breast lesions and 23 apparently healthy controls. ELISA method has been used for estimation the level of IL-6 and IL-10 in serum of three studied groups. Results: There was an elevation of IL-6 and IL-10 level in the sera of BC patients with significant differences between BC and controls (p